Exploring the associations between resilience, dispositional hope, preventive behaviours, subjective well-being, and psychological health among adults during early stage of COVID-19 - Yıldırım, Murat; Arslan, Gökmen (Current psychology (New Brunswick, N.J.), 2022)
During the pandemic, people may experience various mental health problems. Psychological strengths may help them to cope with emerging challenges and foster mental health and well-being. This study examined the associations between resilience, dispositional hope, preventive behaviours, subjective well-being, and psychological health among adults during early stage of COVID-19. A total of 220 participants from general public participated this study completing a battery of measures (134 men [ M age = 42.36 years, SD = 8.99, range = 18 to 60] and 86 women [ M age = 36.73 years, SD = 7.44, range = 18 to 51]). This cross-section study indicated that resilience mediated the relationship between hope and psychological health and subjective well-being. Results also showed that hope, and resilience had significant direct effects on psychological health, and subjective well-being while preventive behaviours did not manifest a significant effect on these two variables except on resilience. Preventive behaviours mediated the relationship between hope and resilience. The results suggest that we should more pay attention to hope and resilience for the development and improvement of well-being and psychological health during the times of crisis.